Ionospheric impact on the geopotential height profile of the temperature by balloon‐borne GPS radiosondes?. Issue 2 (29th January 2013) - Choudhary, R. K.; Rajeev, K.; Krishna Moorthy, K.; Sridharan, R.
<x xml:space="preserve">Abstract</x> [1] We have studied the potential inaccuracies in the geopotential height, its manifestation in the altitude profile of temperature measured by balloon‐borne GPS radiosonde (GPS sonde), and its association with the variations in ionospheric plasma density, particularly in the Indian low latitude region. Using results from a GPS sonde inter‐comparison campaign, conducted at Gadanki (13.5°N, 79.2°E, 6.4°N geomagnetic latitude) at different local times of a day, we show that differences in temperature at different geopotential heights vary with respect to the local time of the day in October 2010. However, differences in temperature become negligible and within the limits of experimental uncertainty if the comparison is made with respect to the time of measurements during the ascent rather than with respect to the GPS‐derived geopotential height. We show that the origin of the mismatch rests with the inaccurate estimation of geopotential height by the two GPS sondes and not due to any inaccuracy in their measurements itself. Differences in the geopotential height estimates are larger during late afternoon, resulting in larger temperature differences between the sondes, and least during late evening/early morning hours. The uncertainty in the geopotential height estimation remains well synchronized with the magnitude and variations in the total electron content (TEC) of the ionosphere. This study exhorts us to account for the local ionospheric variations while extracting the geopotential height profiles of temperature from GPS sonde measurements, especially in the low and equatorial regions where there are large spatial and temporal variations in the ionospheric densities.